2020
DOI: 10.3390/nano10091808
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for the Non-Covalent Amine Functionalization of Carbon-Based Surfaces for Use in Biosensor Development

Abstract: Affinity biosensors based on graphene field-effect transistor (GFET) or resistor designs require the utilization of graphene’s exceptional electrical properties. Therefore, it is critical when designing these sensors, that the electrical properties of graphene are maintained throughout the functionalization process. To that end, non-covalent functionalization may be preferred over covalent modification. Drop-cast 1,5-diaminonaphthalene (DAN) was investigated as a quick and simple method for the non-covalent am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…This is suggested by the large sp 2 carbon peak at 284 eV, which represents the C=C component in graphene [ 80 ], whilst the additional peaks representative of sp 3 carbon, C-O, and C=O at 284.79, 285.48, and 286.12 eV, respectively, are minimal, with the calculated area of sp 2 carbon representing 94.44% of the total area of the spectra [ 30 , 81 ]. However, after processing the graphene into graphene devices, the presence of C-C sp 3 , C-O, and C=O peaks increase, with the formation of additional C-N [ 27 , 82 ], C-O-C, and O-C=O bonds at 285.42, 286.73, and 290.35 eV [ 30 , 81 ], respectively. The peak area of sp 2 carbon also greatly decreases, only amounting to 57.16% of the total area of the carbon spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is suggested by the large sp 2 carbon peak at 284 eV, which represents the C=C component in graphene [ 80 ], whilst the additional peaks representative of sp 3 carbon, C-O, and C=O at 284.79, 285.48, and 286.12 eV, respectively, are minimal, with the calculated area of sp 2 carbon representing 94.44% of the total area of the spectra [ 30 , 81 ]. However, after processing the graphene into graphene devices, the presence of C-C sp 3 , C-O, and C=O peaks increase, with the formation of additional C-N [ 27 , 82 ], C-O-C, and O-C=O bonds at 285.42, 286.73, and 290.35 eV [ 30 , 81 ], respectively. The peak area of sp 2 carbon also greatly decreases, only amounting to 57.16% of the total area of the carbon spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The electropolymerisation of DAN creates a polymer film across the graphene surface, which introduces -NH 2 functional groups on the graphene surface, allowing for antibodies to bind to the amine groups for sensing purposes. It has been reported that pDAN is very robust, capable of remaining on the graphene surfaces after multiple subsequent washes due to strong Van der walls forces [ 27 ]. The electrochemical polymerisation process of polymerising DAN through CV [ 30 , 85 ] uses dilute H 2 SO 4 as the electrolyte for covalently binding the monomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, a 2D nanomaterial composed of a single layer of sp 2 hybridised carbons, possesses superior electrical properties such as high carrier mobility and electron transfer rates at room temperature [30], which present opportunities for applications in a diverse range of fields such as medical, solar cells, energy storage, transparent electrodes, transistors and nanocomposites [31]. In particular, graphene-based sensing devices have features such as label-free detection, high sensitivity and selectivity, biocompatibility and ease of functionalization [32][33][34]. The ability to fabricate graphene devices using standard lithographic processes presents significant advantages over CNT-based sensors in terms of reliability of device platforms and potential multiplexing capability for any bioelectronic nose.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our recent work already demonstrated that improving and optimising the amine surface coverage onto the support system (carbon, graphene, etc) would improve the sensor performance by improving the antibody immobilisation via carbodiimide reaction [ 17 , 40 , 41 , 42 ]. In addition, the utilisation of carboxylic acid groups of antibodies for binding also prevents the potential loss of biological activity of the antibody fragment.…”
Section: Introductionmentioning
confidence: 99%